2018
DOI: 10.22161/ijeab/3.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Study on Genetic Variability, Heritability, Genetic Advance and Correlation among different characters in tomato (Solanum lycopersicum L.)

Abstract: Abstract-The present investigation entitled "Studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
3
9
0
Order By: Relevance
“…Bhandari et al (2017) reported very high heritability estimates for all traits. Moreover, our results agree with those obtained by Singh and Singh (2018), as they reported high heritability estimates for plant height, average fruit weight, TSS, number of fruits per plant, and weight of fruits per plant. On the contrary to our results, they found low heritability estimates for number of fruits per truss.…”
Section: Genetic Variability and Heritabilitysupporting
confidence: 92%
See 2 more Smart Citations
“…Bhandari et al (2017) reported very high heritability estimates for all traits. Moreover, our results agree with those obtained by Singh and Singh (2018), as they reported high heritability estimates for plant height, average fruit weight, TSS, number of fruits per plant, and weight of fruits per plant. On the contrary to our results, they found low heritability estimates for number of fruits per truss.…”
Section: Genetic Variability and Heritabilitysupporting
confidence: 92%
“…Also, Sidhya et al (2014) found medium PCV and GCV for plant height, while, in contrast to our findings, they reported medium PCV and GCV for number of fruits per plant and weight of fruits per plant. Singh and Singh (2018) agree with our results for plant height, number of fruits per truss, average fruit weight, number of fruits per plant, weight of fruits per plant, and TSS. Moreover, Saravanan et al (2019) found high PCV and GCV for number of fruits per plant.…”
Section: Genetic Variability and Heritabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly low amount of PCV and GCV for harvest duration and days to marketable maturity were also observed by Ara et al, (2009) and Patel et al, (2013). Kumar (2014), Singh et al, (2015) and Singh and Singh (2019) reported low phenotypic and genotypic coefficients of variation for days to 50 % flowering.…”
Section: Moderatementioning
confidence: 99%
“…The mean square due to genotypes were highly significant for all traits (P < 0.01) except for days to 50% flowering, plant height, number of branches per plant, number of fruits per cluster and pericarp thickness which were significant at (P < 0.05), indicating the presence of sufficient genetic variability in the genotypes and considerable scope for their improvement Table 1. According to Asati, et al [17] analysis of variance revealed that significant differences among the genotypes for all the traits; Aysh, et al [18] reported that the highly significant differences observed among the genotypes evaluated indicates existence of a good deal of variability with respect of the characteristics assessed and offers ample chances for the genetic improvement of the tomato germplasm; Meena and Bahadur [19] reported that there were significant differences among germplasm for all the traits studies indicating the presence of significant variability in the materials which can be exploited through selection; Shankar Shankar, et al [20]; Haydar, et al [21] and Singh, et al [22] revealed that highly significant differences among the genotypes for all the characters indicating sufficient variability existed in the present material selected for the study and indicating the scope for selection of suitable initial breeding material for crop improvement; Kumar, et al [23] reported that significant differences among germplasm for all the traits studies indicating the presence of significant variability in the materials which can be exploited through selection.…”
Section: Analysis Variancementioning
confidence: 99%